2012
DOI: 10.1038/cddis.2012.60
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 agonists induced cell death in Burkitt's lymphoma cells is variable and influenced by TLR9 polymorphism

Abstract: Toll-like receptor 9 (TLR9) triggering is a promising novel strategy to combat cancer as it induces innate and adaptive immunity responses. B-cell lymphoma is unique in this context as tumor cells express TLR9 and may harbor latent Epstein-Barr virus (EBV), a gamma-herpesvirus with remarkable oncogenic potential when latent. Latent EBV may be promoted by TLR9 triggering via suppression of lytic EBV. Here, we elaborated an initial assessment of the impact of TLR9 triggering on EBV-positive and EBV-negative B-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 37 publications
0
20
2
Order By: Relevance
“…After reviewing full text, 10 studies were excluded for the following reasons, three papers were reviews [5], [11], [36], two papers were relating to risk of infection during cancer therapy [37], [38], one paper was relating to outcome of AML patients transplanted from HLA-identical sibling donors [39], two papers lacked of gene frequency data to calculate the ORs and 95% CI [40], [41], and two of the studies were disequilibrium from HWE in control group [13], [15]. One article evaluated two SNPs (rs352140 and rs5743836) with Burkitt’s lymphoma risk [24], and genotype distribution in the control of rs352140 was inconsistent with HWE (P<0.05). Therefore, we extracted the data relating to rs5743836 for our meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After reviewing full text, 10 studies were excluded for the following reasons, three papers were reviews [5], [11], [36], two papers were relating to risk of infection during cancer therapy [37], [38], one paper was relating to outcome of AML patients transplanted from HLA-identical sibling donors [39], two papers lacked of gene frequency data to calculate the ORs and 95% CI [40], [41], and two of the studies were disequilibrium from HWE in control group [13], [15]. One article evaluated two SNPs (rs352140 and rs5743836) with Burkitt’s lymphoma risk [24], and genotype distribution in the control of rs352140 was inconsistent with HWE (P<0.05). Therefore, we extracted the data relating to rs5743836 for our meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Study characteristics were summarized in Table 1. As shown in table 1, five studies were available for rs352140 [14], [16], [17], [22], [23], ten studies were available for rs5743836 [16], [20], [22], [24][27], and four studies were available for rs187084 [2], [16], [26], [27]. Those include studies in Germany, Poland, Netherlands, Greece, Croatia, Portugal, USA, Australia, India and China.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that TLR-9 engagement on cluster of differentiation 4-positive (CD4 + ) T cells can enhance their survival and therefore potentiate anticancer responses by prolonging T-cell activity 14. Previous studies have indicated that TLR-9 polymorphisms may be associated with the risk of developing several types of cancers, including bladder cancer,15 prostate cancer,1618 acute lymphoblastic leukemia,19 hepatocellular carcinoma,20 gastric cancer,21,22 cervical cancer,23 Hodgkin’s lymphoma,24 breast cancer,25 Burkitt’s lymphoma,26 non-Hodgkin’s lymphoma,27 endometrial cancer,28 esophageal cancer,23 and lymphoma 24,27,29. However, the results are inconsistent and inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…We reviewed the titles, abstracts, and full texts of all retrieved articles through defined criteria. Finally, 19 articles were included in this study (Nieters et al, 2006;Etokebe et al, 2009;Hold et al, 2009;Mollaki et al, 2009;Ashton et al, 2010;Pandey et al, 2011;Zeng et al, 2011;Chen et al, 2012;Carvalho et al, 2012;Li et al, 2012;Mandal et al, 2012;Miedema et al, 2012;Noack et al, 2012;Roszak et al, 2012;Xie et al, 2012;Lai et al, 2013;Resler et al, 2013;Singh et al, 2013;. Since more than one case-control study was included in ten articles (Nieters et al, 2006;Hold et al, 2009;Mollaki et al, 2009;Ashton et al, 2010;Carvalho et al, 2012;Li et al, 2012;Miedema et al, 2012;Roszak et al, 2012;Lai et al, 2013;Resler et al, 2013), they were considered as separate studies in the meta-analysis.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%